2022
DOI: 10.21873/invivo.12843
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Drug Combinations Modify Cisplatin-induced Acute Kidney Injury

Abstract: Background/Aim: There is limited evidence about the nephrotoxicity of calcium channel blockers (CCBs) and renin-angiotensin system (RAS) inhibitors with concomitant cisplatin (CDDP). We investigated whether combinations of antihypertensive drugs are associated with CDDP-related acute kidney injury (AKI) using the Japanese Adverse Drug Event Report database. Patients and Methods: We analysed 544,864 reports in the database from 2004 to 2020. A reporting odds ratio (ROR) and confidence interval (CI) with adjustm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…These cardiac treatments are known to affect afferent or efferent renal arterioles tonus and many interfere with OCT2 and MATE [ 57 ] which may alter with cisplatin elimination. In this sense, Takeuchi et al [ 54 ] reported a cumulative cisplatin related AKI-risk with the concomitant administration of several classes of antihypertensive treatments. However, the administration of antihypertensive therapies implies patient is suffering from an underlying hypertensive or cardiovascular disease, and the addition of extra cardiac treatment suggest a more serious trouble.…”
Section: Discussionmentioning
confidence: 99%
“…These cardiac treatments are known to affect afferent or efferent renal arterioles tonus and many interfere with OCT2 and MATE [ 57 ] which may alter with cisplatin elimination. In this sense, Takeuchi et al [ 54 ] reported a cumulative cisplatin related AKI-risk with the concomitant administration of several classes of antihypertensive treatments. However, the administration of antihypertensive therapies implies patient is suffering from an underlying hypertensive or cardiovascular disease, and the addition of extra cardiac treatment suggest a more serious trouble.…”
Section: Discussionmentioning
confidence: 99%